Shakespeare's clown-fools revisited with an oriental escort: A reconsideration of Falstaff, Lear's Fool, Cleopatra's clown, and an examination in this light of a clown-fool of Sanskrit drama - Ray, Ratna (University of Ottawa (Canada), 1970)
Abstract not available.
Keywords: Literature, Comparative.; Literature, English.